Burkina Faso : First Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for a Waiver of Nonobservance of Performance Criterion-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Burkina Faso. (IMF Staff Country Reports; Country Report ;, 2010)
Economic recovery has gained momentum, and short-term prospects have improved. Program implementation is good. Fiscal consolidation is essential for Burkina Faso's macroeconomic stability and debt sustainability. Structural reforms remain focused on a few priority areas supporting growth and macroeconomic stability. Terms-of-trade and weather-related shocks are the main risks to the economic outlook. Executive Directors commend the government for their commitment to sound policies and encourage them to proceed with the reform agenda. The government also needs to sustain revenue mobilization to improve fiscal sustainability.